Technological limitations of solid-source chemical vapor deposition of van der Waals heterostructures - Jakub Sitek; Wojciech Sitek; Ben R. Conran; Xiaochen Wang; Clifford McAleese; Anna Kaleta; Slawomir Kret; Iwona Pasternak; Mariusz Zdrojek; Wlodek Strupinski (Scientific Reports)
Abstract The large-scale synthesis of van der Waals heterostructures (vdWHSs) is required to adopt these materials in electronic devices. However, the repeatable and controllable growth of vdWHSs has proven challenging. Here, we investigate the technological aspects of solid-source chemical vapor deposition (CVD) of two-dimensional heterostructures, with WS2/graphene and MoS2/graphene as examples. We show that by modification of one variable at least one another is unintentionally altered. For example, change in the growth pressure influences the evaporation rate of sulfur and shifts the position of one of the growth zones. We also perform a statistical screening of the 11 process parameters, indicating which of them impact the evaporation of the precursors. The screening indicates that the evaporation depends on weight of growth promoter (NaCl), growth temperature, precursors temperature, time difference between main and sulfur growth zones reaching the set temperatures, pressure, carrier gas flow, and process time. Finally, the five consecutive, identical growth processes show the seemingly inherent variability in synthesizing vdWHSs. We suggest that the high but limited airtightness of the CVD system or the substrate features can cause repeatability issues. Our study can facilitate future research on van der Waals heterostructures growth.